2021
DOI: 10.1161/circresaha.121.318908
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Chaperone-Mediated Autophagy Promotes Inflammation and Atherosclerosis

Abstract: Rationale: The NLRP3 (NLR [NOD-like receptor] family, pyrin domain containing 3) inflammasome is an important driver of atherosclerosis. Our previous study shows that chaperone-mediated autophagy (CMA), one of the main lysosomal degradative process, has a regulatory role in lipid metabolism of macrophages. However, whether the NLRP3 inflammasome is regulated by CMA, and the role of CMA in atherosclerosis remains unclear. Objective: To determine the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 51 publications
0
65
0
Order By: Relevance
“…In previous studies, autophagy was shown to play a substantial role in the pathogenesis of atherosclerosis [13,14]. To that end, we investigated the possible association between rutin and autophagy-related proteins using western blot analysis and electron microscopy.…”
Section: Rutin Can Promote Autophagy In Macrophagesmentioning
confidence: 96%
“…In previous studies, autophagy was shown to play a substantial role in the pathogenesis of atherosclerosis [13,14]. To that end, we investigated the possible association between rutin and autophagy-related proteins using western blot analysis and electron microscopy.…”
Section: Rutin Can Promote Autophagy In Macrophagesmentioning
confidence: 96%
“…The NLRP3 inflammasome can also be activated by oxidative or apoptosis-induced mtDNA, which is released during autophagy repression ( Sollberger et al, 2015 ). Impaired CMA has also been proven to increase NLRP3 inflammasome activation and secretion of IL-1β, promoting vascular inflammation and atherosclerosis ( Qiao et al, 2021 ). Therefore, autophagy can negatively regulate pyroptosis by restraining the activation of the inflammasome and caspase-1/GSDMD pathway ( Wang X. et al, 2020 ).…”
Section: Possible Association Between Autophagy and Pyroptosis In Atherosclerosismentioning
confidence: 99%
“…TAMs seem to produce IL-17 to activate CMA and become tolerant to apoptosis-inducing treatments in cancer [ 81 ]. Hence, normal macrophages seem to need the inhibition of CMA activity to promote inflammatory responses through inflammasome activation ( Figure 3 A) [ 29 ].…”
Section: Possible Therapeutic Approaches Based On Cma Inhibition In P...mentioning
confidence: 99%
“…CMA activity is highly regulated by cell context and thereby the stimuli that the cell receives, as these modulate the amount of functional LAMP-2A that is mobilized to the lysosomal membrane [ 21 , 22 ]. CMA is an essential quality control system for specific proteins, contributes to the supply of amino acids during long starvation periods, controls proteome remodeling in response to cell context [ 24 , 25 , 26 , 27 ], and, when dysregulated, affects cellular functions leading to diseases such as cancer [ 20 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%